28‐1: Invited Paper: Effect of Channel Defining Layer on the Vertical Oxide TFTs for the Application to the Ultra High Resolution Display. Issue 1 (May 2017) - Lee, Seung-Hee; Lee, Kwang-Heum; Nam, Yunyong; Ko, Jong-Beom; Yeom, Hye-In; Hwang, Chi-Sun; Park, Sang-Hee Ko
Abstract : We investigated the effect of back channel material which plays as a channel defining layer in vertical TFT for the application to the TFT of ultra‐high resolution display. Although the IGZO vertical TFT with polyimide back channel has low mobility, it shows good on/off ratio higher than 10 7, low gate leakage current, and hard saturation behavior with channel length of 1 um.